2012
DOI: 10.1074/jbc.m111.329219
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Aquaporin Translocation Regulates Cellular Water Flow

Abstract: Background: Aquaporin channels ensure appropriate membrane permeability to water in all cells.Results: Following a hypotonic stimulus, subcellular localization of aquaporin 1 occurs via a mechanism dependent on transient receptor potential channels, extracellular calcium influx, calmodulin, and the phosphorylation of two threonines (157 and 239) of aquaporin 1.Conclusion: Rapid translocation of aquaporin 1 regulates membrane water permeability.Significance: This mechanism may serve as a prototype for the rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…In another study, researchers have demonstrated that ultraviolet radiation (UVB) and H 2 O 2 induced AQP1 down-regulation which was mediated by ERK activation, however, the mechanism was not mentioned in this article [50]. Our results may explain the effect of ERK pathway in translocation and down-regulation of AQP1.There are still distinct findings to identify signaling pathway associated with trafficking of AQP1, such as one recent study reported that AQP1 trafficking was mediated by the tonicity of the cell environment in a specific PKC- and Ca 2+ -dependent manner [16], [17]. Therefore, signaling cascades for translocation of AQP1 still need further examination.…”
Section: Discussionmentioning
confidence: 64%
“…In another study, researchers have demonstrated that ultraviolet radiation (UVB) and H 2 O 2 induced AQP1 down-regulation which was mediated by ERK activation, however, the mechanism was not mentioned in this article [50]. Our results may explain the effect of ERK pathway in translocation and down-regulation of AQP1.There are still distinct findings to identify signaling pathway associated with trafficking of AQP1, such as one recent study reported that AQP1 trafficking was mediated by the tonicity of the cell environment in a specific PKC- and Ca 2+ -dependent manner [16], [17]. Therefore, signaling cascades for translocation of AQP1 still need further examination.…”
Section: Discussionmentioning
confidence: 64%
“…Under normal conditions, approximately 90 % of the filtered volume of water is reabsorbed in the proximal tubule and the thin descending limb of Henle's loop via constitutively expressed AQP1 water channels. Acute regulation of AQP1 is controversial [13]. Water reabsorption in the connecting tubule (CNT) and collecting duct (CD) is under the control of AVP and other signaling molecules and occurs via the apical AQP2 and the basolateral AQP3 and AQP4 water channels.…”
mentioning
confidence: 99%
“…35 Hypotonicity-induced translocation of AQP1 has also been described in HEK293 cells. 36 Another example that illustrates the role of AQPs in cell volume regulation can be seen in sperm, where AQP3 is actively involved in the signaling pathway that activates RVD to protect sperm from excess cell swelling, thereby optimizing postcopulatory sperm behavior. In line with this, the RVD of sperm of AQP3 ¡/¡ mice was inhibited compared to wild-type mice and these knockout mice had lower fertility.…”
Section: Aqps and Cell Volumementioning
confidence: 99%